Development of Kifilideen’s Elimination Matrix Model to Solve Simultaneous Equations of Four Variables (w, x, y, and z), Three Variables (x, y, and z), and Two Variables (x and y) - Osanyinpeju, Kifilideen (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The Gaussian elimination method of solving four variables of simultaneous equations involves eliminating some elements of the simultaneous equations in triangular form to zero to determine the values of the variables of the simultaneous equations. This approach does not involve a matrix in generating the values of variables of the simultaneous equations. There is a need to develop a matrix model for solving four variables of simultaneous equations. The pattern of the developed model can be extended by solving three variables and two variables of simultaneous equations. This study develops Kifilideen’s Elimination Matrix Model to solve simultaneous equations of four variables w, x, y, and z, three variables x, y, and z and two variables x and y. The elimination method was gradually used to reduce the number of variables of a given simultaneous equation in matrix form. In contrast, in the process, Kifilideen’s Elimination Matrix Model was generated to solve the values of the variables of the simultaneous equations. The Kifilideen’s Elimination Matrix Model was implemented in solving four variables w, x, y, and z, three variables x, y, and z and two variables x and y simultaneous equations. Kifilideen’s Elimination Matrix Model has been fully utilised, attractive, accurate, and easy to understand